Soybean and avocado unsaponifiables: a review of their potential use in the treatment of osteoarthritis - Sabucedo-Suárez, Ana; López-Peña, Mónica; Permuy, María; Muñóz, Fernando (Frontiers in Veterinary Science, 2025)
Recent research has shown that Avocado-Soybean Unsaponifiables (ASU) greatly reduce the symptoms of osteoarthritis (OA). It’s yet unknown exactly how ASU works, however, it has been demonstrated to have analgesic and anti-inflammatory effects. These qualities can potentially lessen the need for non-steroidal anti-inflammatory medicines (NSAIDs) and their secondary effects. This review aims to examine the current literature on ASU, focusing on their efficacy, mechanism of action, and potential utility in treating OA for managing chronic pain associated with this condition. The literature review was conducted manually through Pubmed, Scopus and Web of Science (WOS) databases, covering studies from 2000 to 2022 with terms like “osteoarthritis,” “OA,” “animal models,” “ASU,” and “soy/avocado.” Two reviewers independently screened each article using inclusion and exclusion criteria and categorized the studies into in vitro, preclinical, and clinical groups. According to in vitro research, ASU affect the regulation of molecules related to OA, increasing structural elements like collagen and aggrecan and decreasing pro-inflammatory mediators. Although results vary, pre-clinical research in different animal models has demonstrated positive effects, such as ameliorating histopathological changes and reduced inflammation. Despite some discrepancies regarding structural changes in the joints, clinical trials typically demonstrate symptom relief and slow down the disease progression. While ASU demonstrates significant promise in alleviating OA symptoms and reducing reliance on NSAIDs, further research is essential to fully understand its mechanisms of action. More studies are needed to determine the precise pathways through which ASU exerts its effects and to establish the most effective dosages for its administration, either alone or in combination with other treatments.